Teaching in Uncharted Waters: Seeking Critical Body Literacy Scripts (Alberta Journal of Educational Research, 2012)
Schools are places of learning, but they are also sites of struggle when fitness, obesity, and body image issues converge for students and teachers. Responding to teachers’ concerns about their students on diets, a Canadian teachers’ organization produced a body image program which included a training day for schools undertaking whole-school implementation. The teachers’ organization commissioned research to determine program outcomes. The research team interviewed 48 participating teachers. Data include: teacher responses to a post-training survey, interview transcripts, and artefacts from school visits. Findings indicate that implementation is impacted by resources and the complex ways that students’ and teachers’ bodies are positioned socially. While the program intent was to provide teachers with body image lessons, findings suggest that other supports are needed such as knowledge mobilization of body image research, critical framing to respond to issues, and a theoretical map such as critical body literacy in order to navigate these uncharted waters. Les écoles constituent des lieux d’apprentissage; pourtant, elles sont également des sites où convergent des questions portant sur l’aptitude physique, l’obésité et l’image corporelle et ce, tant pour les élèves que les enseignants. En réaction aux préoccupations des enseignants relatives aux élèves qui suivent des régimes amaigrissants, une organisation regroupant des enseignants canadiens a créé un programme portant sur l’image corporelle et qui comprend une journée de formation pour les écoles prêtent à entreprendre une mise en œuvre à l’échelle de l’école. L’organisation des enseignants a mandaté une étude pour déterminer les résultats du programme. L’équipe de recherche a interviewé 48 enseignants. Parmi les données recueillies, notons : les réponses des enseignants au sondage effectué après la formation, les transcriptions d’interviews et des artéfacts découlant des visites d’écoles. Les conclusions indiquent que la mise en œuvre est influencée par les ressources et par les façons complexes dont sont socialement reconnus les corps des élèves et les enseignants. Alors que les objectifs du programme consistaient à fournir aux enseignants des leçons sur l’image corporelle, les résultats portent à croire qu’il faut avoir d’autres appuis comme la mobilisation du savoir découlant de la recherche sur l’image corporelle, la définition du cadre critique selon lequel réagir aux questions, et une carte théorique (connaissance critique du corps, par exemple) de sorte à pouvoir naviguer ces eaux inconnues.